The Visual Search Strategies Underpinning Effective Observational Analysis in the Coaching of Climbing Movement - Mitchell, James; Maratos, Frances A.; Giles, Dave; Taylor, Nicola; Butterworth, Andrew; Sheffield, David (Frontiers in Psychology, 2020)
Despite the importance of effective observational analysis in the technical aspects of climbing performance, limited research informs this aspect of climbing coach education. Thus, the purpose of the present research was to explore cognitive-perceptual mechanisms underpinning visual search strategies of expert and novice climbing coaches through the novel combination of eye-tracking technology and retrospective think-aloud methodology. Analysis of gaze data revealed expert climbing coaches to demonstrate fewer fixations of greater duration, and fixate on distinctly different areas of the visual display, than their novice counterparts. Retrospective think-aloud interviews further demonstrated differences in the cognitive-perceptual mechanisms underpinning these visual search strategies, with expert coaches more cognisant of their visual search strategy. To expand, the gaze behaviour of expert climbing coaches was underpinned by hierarchical and complex knowledge structures relating to principles of climbing movement. This enabled expert coaches to actively focus on the most relevant aspects of a climber’s performance for analysis. Findings demonstrate the utility of combining eye tracking and retrospective think-aloud interviewing as a new, efficient methodology of capturing the cognitive-perceptual processes of climbing coaches to inform coaching education/strategies.